2013
DOI: 10.5551/jat.14860
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Adding Ezetimibe to Fluvastatin on Kidney Function in Patients with Hypercholesterolemia: a Randomized Control Trial

Abstract: Aims:Statins not only reduce low-density lipoprotein (LDL) cholesterol, but also prevent the progression of kidney dysfunction. Ezetimibe, a cholesterol-absorption inhibitor, also lowers LDL cholesterol levels when added to statins; however, the effect of add-on ezetimibe on kidney function has had conflicting results. Methods:We conducted an open-labeled, randomized, 12-month trial, comparing the effects of daily therapy with 20 mg fluvastatin either with or without 10 mg ezetimibe in 54 patients with dyslipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…In the ENHANCE study, patients with heterozigous FH were randomized to simvastatin 80 mg with either placebo or ezetimibe 10 mg. In line with previous trials with ezetimibe in non FH hypercholesterolemic patients [160][161][162]167], addition of ezetimibe to the statin did not result in significant differences in C-IMTp despite a greater reduction in LDL-C levels [168].…”
Section: Control Of Dyslipidemia and C-imtpsupporting
confidence: 87%
See 1 more Smart Citation
“…In the ENHANCE study, patients with heterozigous FH were randomized to simvastatin 80 mg with either placebo or ezetimibe 10 mg. In line with previous trials with ezetimibe in non FH hypercholesterolemic patients [160][161][162]167], addition of ezetimibe to the statin did not result in significant differences in C-IMTp despite a greater reduction in LDL-C levels [168].…”
Section: Control Of Dyslipidemia and C-imtpsupporting
confidence: 87%
“…Worth noting, several studies included in this review (n=24 out of 161 studies) did not find associations between traditional risk factors and C-IMTp or favorable changes in C-IMTp with interventions that reduce the alluded risk factors. However, a detailed scrutiny of these studies allowed us to identify, in most cases, one or more explanations to these negative results: a) the population was very young and had baseline IMT in the normal range [51,64]; b) the time of observation was relatively short (1 year) to detect significant associations or changes in the sample investigated [51,64,93,94,167] and/or c) IMTp was evaluated only in the distal 1 cm of the common carotid artery, a segment hardly affected by atherosclerosis [24,40,42,43,51,64,81,84,92,122,123]. Actually, negative studies without one or more of these features (3 observational[49,74,112] and 5 interventional [56,57,95,101,152] were uncommon, which underline the importance of an attentive consideration of methodological aspects in the design of studies aimed to ascertain the clinical significance of C-IMTp.…”
Section: So Are Traditional Risk Factors Causative Of Accelerated C-mentioning
confidence: 99%
“…Similar to studies assessing the relationship between lowering LDL cholesterol and renal function, the results of these studies were also controversial. Small-scale open-label randomized studies conducted by Japanese researchers reported that adding ezetimibe to Fluvastatin or Pitavastatin produced significant improvement in proteinuria or eGFR changes for 12 or 6 months [26,27]. However, another open-labeled randomized 12-month trial of 286 patients with dyslipidemia showed no significant difference in serum creatinine and albuminuria changes between the statin uptitration group and the statin + ezetimibe group [29].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to cardiovascular outcomes, ezetimibe could be assumed to have beneficial effects on renal outcomes, because it has been reported to activate autophagy and inhibit inflammatory response [23,24], which are closely linked with CKD [25]. Researchers have investigated whether ezetimibe combined with a statin was more protective for renal function than statin monotherapy, but their results were inconsistent [26][27][28][29]. However, most previous studies were small in size, of short duration, or included unique subjects, such as perioperative patients.…”
Section: Introductionmentioning
confidence: 99%
“…In total, 40 RCTs reported about the effect of statins on change of eGFR 1315,27,2963 , of which 30 compared a statin to control, and 10 compared two or more statins with each other. The effect of statins on proteinuria was reported in 25 RCTs 13,14,28,29,32–34,36,39,45,46,4854,57,60,6265 , of which 19 compared a statin to control intervention, and six compared two or more statins. Characteristics of included RCTs are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%